Rechtsfragen bei Open Science Ein Leitfaden - Kreutzer, Till (Hamburg University Press, 2021)
Digitisation enables open science. Digitisation has many aspects, in particular free access to scholarly publications and materials (Open Access), transparent review procedures (Open Peer Review) or open source technologies (Open Source). The programme Hamburg Open Science (duration 2018-2020) supports, among other things, cultural change in research. It is in this context that the present guide was created. It is intended to make the legal environment tangible. The guide first systematically elaborates the relevant areas of law. The second part answers legal questions about Open Science that come directly from universities and libraries. In this way, the guide is prepared and communicated in a practical manner. The authors of the guide are Dr. Till Kreutzer, partner at the law firm iRights.Law, and their research assistant Henning Lahmann. This second, completely revised and expanded edition was produced with the assistance of Dr. Ina Kaulen, Hamburg State and University Library Carl von Ossietzky.